Photolysis of methicillin-resistant Staphylococcus aureus using Cu-doped carbon spheres. (2nd October 2020) - Xi, Juqun; An, Lanfang; Wei, Gen; Huang, Yaling; Li, Dandan; Fan, Lei; Gao, Lizeng
Abstract : Cu-HCSs in combination with blue-light irradiation promoted photobleaching of STX to destroy membrane integrity, and further caused oxidative cleavage of DNA and proteins inside MRSA, resulting in efficient killing of MRSA. Abstract : Developing alternative treatment strategies against methicillin-resistant Staphylococcus aureus (MRSA) infections is a challenge but could have many potential applications. In this paper, we developed a novel approach to eradicate MRSA through photolysis of the staphyloxanthin (STX) pigment found within the MRSA membranes and intracellular molecules ( e.g. genomic DNA and proteins). Specifically, Cu-doped hollow carbon spheres (Cu-HCSs) were employed here for antibacterial treatment. Unlike blue-light treatment alone, which only "injured" MRSA, Cu-HCSs in combination with blue-light irradiation promoted photobleaching of STX to destroy membrane integrity, and further caused oxidative cleavage of DNA and proteins inside MRSA, working as a nuclease/protease mimicking nanozyme, resulting in efficient killing of MRSA. Mechanism analysis showed that the cleavage activity resulted from the elevated levels of singlet oxygen ( 1 O2 ) generated from the photosensitized oxidation of Cu-HCSs. Further animal studies demonstrated that the photolysis activity of Cu-HCSs could be used to treat subcutaneous abscesses and bacteremia caused by MRSA. Thus, this photolysis-based antibacterial platform may help avoid bacterial resistance, with the potential to kill multidrug resistant bacteria.